2018
DOI: 10.3390/en11092302
|View full text |Cite
|
Sign up to set email alerts
|

Social and Infrastructural Conditioning of Lowering Energy Costs and Improving the Energy Efficiency of Buildings in the Context of the Local Energy Policy

Abstract: The main problem in creating successful efficiency improvement policies is adjusting objectives to local development programs, dependent on public awareness. This article attempts to find a framework for the costs of changing energy policies using neural networks to identify the social-infrastructure conditions. An analysis model is presented of social-infrastructure conditions of energy costs reduction and buildings’ efficiency improvement. Data were obtained from standardized interviews with Zielona Góra, Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The work to date indicates that, starting from the stage of announcing the tender procedure for construction works, one should be aware of the risk of exceeding the assumed resources, in particular the adopted budget [38]. This assumption is confirmed by other works that suggest improving the estimation of costs of the planned investment and optimization of their spending during the investment [39,40].…”
Section: Introductionmentioning
confidence: 83%
“…The work to date indicates that, starting from the stage of announcing the tender procedure for construction works, one should be aware of the risk of exceeding the assumed resources, in particular the adopted budget [38]. This assumption is confirmed by other works that suggest improving the estimation of costs of the planned investment and optimization of their spending during the investment [39,40].…”
Section: Introductionmentioning
confidence: 83%
“…In addition, Mrówczyńska et al (2018) defined that energy efficiency depends on many factors, such as climate, building design, materials, technology, energy carriers, how heat is applied and the tightness of bulk heads, but also depends on national and local policies (Gorbacheva and Sovacool 2015). The determinants of energy use vary depending on perceptions of each user, however, in general it can be said that financial factor play an important role in influencing behavior of energy use, thus it should be considered in any strategy for increasing energy efficiency.…”
Section: Factors That Impact On Energy Efficiencymentioning
confidence: 99%
“…Furthermore, driving towards a low carbon economy is a clear opportunity for global economy, jobs and sustainable growth. There are numerous studies related to energy efficiency but the approaches, perspectives and contexts are very diverse such as Mrówczyńska et al (2018) with "Social and infrastructural conditioning of lowering energy costs and improving the energy efficiency of buildings in the context of the local energy policy" for building sector; Chwieduk and Chwieduk (2020) with "determination of the energy performance of a solar low energy house with regard to aspects of energy efficiency and smartness of the house" which typically household sector; Dato (2018) "investment in energy efficiency, adoption of renewable energy and household behavior" for household sector; Cini et al (2017) "Energy Efficiency Projects of Budget Beneficiaries And Its Impact On Regional Economy" for economic related; Strielkowski et al (2019) with "innovative policies for energy efficiency and the use of renewables in households" for household sector; Cristescu et al (2017) with "increasing energy efficiency and optimizing the operation of systems that produce clean energy from renewable sources"; Stagnitta et al (2020) with "A complementary approach to traditional energy balances for assessing energy efficiency measures in final uses: The case of space heating and cooling"; Lenzi et al (2013) with "From energy balance to energy efficiency indicators including water losses"; Benavente-Peces (2019) with "On the energy efficiency in the next generation of smart Buildings Supporting technologies and techniques" for building sector; Han et al (2017) with "measuring energy efficiency in China's transport sector" for transport sector. However, research on specific factors affecting energy efficiency are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, efficient energy management should provide energy not only for current generations but also for the future [4], and such management should minimize negative impact on the environment [5,6]. The increased use of energy from renewable energy sources is also an important part of the potential societal options in the event of failure of what have become traditional energy systems [7]. Supporting the development of RES has become an important policy objective of the European Union [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it can be observed that political incentives are necessary in order to increase the use of forest biomass [11]. Addressing social acceptance will be a prerequisite for the success of initiatives or legislation to achieve this potential [7,17,18].…”
Section: Introductionmentioning
confidence: 99%